Dampak dan Keberlanjutan Program Cetak Sawah di Kabupaten Katingan, Provinsi Kalimantan Tengah - Lalu Ardhian Mustapa; Yeti Lis Purnamadewi; Arya Hadi Dharmawan (Analisis Kebijakan Pertanian, 2019)
One of the government’s policies to realize food security is the expansion of new rice fields called the rice fields development program. Rice fields development programs carried out outside Java Island are constrained by socio-cultural factors, limited infrastructure for farming facilities, land fertility, market access, labour availability and others. This study aims to analyze the impact and evaluate the sustainability status of rice fields development program in 2016 in Katingan Regency, Central Kalimantan Province. The study was conducted in Katingan Kuala Subdistrict, Katingan Regency, Central Kalimantan Province in May - June 2018 respondent who participate in rice fields development program from the Ministry of Agriculture in 2016. Primary data were collected by interviews with questionnaires on 41 respondents who have deliberately determined farmers and program participants supported by focus group discussions with 10 key informants and observations in the field. Indicators in determining respondents were the area of rice field ownership, farming experience and skills, main income source, education level, and others. While the informant criterion was understanding the social, cultural, institutional, infrastructure and environmental conditions during rice fields development program took place. Rice field development program in Katingan Kuala District, Katingan Regency in 2016 can be implemented as planned. The impact of the rice field development program includes increasing farmers' income, expanding employment opportunities, but not damaging the environment. The increase in income does not increase the welfare of the average farmer because the increase in income only reaches 11.6%. The results of the analysis used the Rapid Appraisal for Farming (RAP-FARM), specifically the Multidimensional Scaling (MDS) approach showed a sustainability index was 54.30. It means that rice fields development program in Katingan Regency was less sustainable because the five sustainability indicators are institutional and infrastructure was less sustainable; while other aspects were quite sustainable with the highest value in the ecological aspects. AbstrakSalah satu kebijakan pemerintah untuk mewujudkan ketahanan pangan adalah perluasan lahan sawah yang disebut dengan program cetak sawah. Program cetak sawah yang dilaksanakan di luar Pulau Jawa terkendala faktor sosial budaya, keterbatasan sarana prasarana usaha tani, kesuburan lahan, akses pasar, ketersediaan tenaga kerja dan lainnya. Penelitian ini bertujuan menganalisis dampak dan mengevaluasi status keberlanjutan cetak sawah tahun 2016 di Kabupaten Katingan, Provinsi Kalimantan Tengah. Penelitian dilakukan di Kecamatan Katingan Kuala Kabupaten Katingan Provinsi Kalimantan Tengah pada bulan Mei - Juni 2018 responden peserta program cetak sawah dari Kementerian Pertanian tahun 2016. Data primer dikumpulkan melalui wawancara dengan kuesioner terhadap 41 responden yang ditentukan secara sengaja dan didukung focus group discussion dengan sepuluh informan kunci serta observasi di lapangan. Program cetak sawah di Kecamatan Katingan Kuala, Kabupaten Katingan tahun 2016 dapat dilaksanakan sesuai dengan yang direncanakan. Dampak program cetak sawah antara lain meningkatkan pendapatan petani, memperluas kesempatan kerja, namun tidak merusak lingkungan. Peningkatan pendapatan tidak sampai meningkatkan kesejahteraan rata-rata petani karena peningkatan pendapatan hanya mencapai 11,6%. Hasil analisis menggunakan Rapid Appraisal for Farming (RAP-FARM), khususnya pendekatan Multidimensional Scaling (MDS) menunjukkan indeks keberlanjutan 54,30. Hal ini berarti program cetak sawah di Kabupaten Katingan kurang berkelanjutan karena dari lima indikator keberlanjutan, yaitu kelembagaan dan infrastruktur kurang berkelanjutan; sementara aspek lainnya cukup berkelanjutan dengan nilai tertinggi pada aspek ekologi.